2022
DOI: 10.3390/ijms232315027
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Roles of Pulmonary Cells in Acute Lung Injury: Lessons from Clinical Practice

Abstract: Interstitial lung diseases (ILD) are relatively rare and sometimes become life threatening. In particular, rapidly progressive ILD, which frequently presents as acute lung injury (ALI) on lung histopathology, shows poor prognosis if proper and immediate treatments are not initiated. These devastating conditions include acute exacerbation of idiopathic pulmonary fibrosis (AE-IPF), clinically amyopathic dermatomyositis (CADM), epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI)-induced lung inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 179 publications
0
2
0
Order By: Relevance
“…Research has shown that heat shock protein-70 (HSP-70) exerts a protective effect against pulmonary fibrosis. However, EGFR-TKIs have been found to suppress HSP-70 expression in the lungs, which may potentially promote pulmonary fibrosis ( Enomoto, 2022 ). Furthermore, the efficacy of EGFR-TKI-induced glucocorticoid treatment in ILD implies a possible link to immune mediation ( Kodama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that heat shock protein-70 (HSP-70) exerts a protective effect against pulmonary fibrosis. However, EGFR-TKIs have been found to suppress HSP-70 expression in the lungs, which may potentially promote pulmonary fibrosis ( Enomoto, 2022 ). Furthermore, the efficacy of EGFR-TKI-induced glucocorticoid treatment in ILD implies a possible link to immune mediation ( Kodama et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another example is DM-ILD. Previous studies reported that ferritin was produced by macrophages [26] and correlated with lung function parameters and survival [27]. IL-18 was also secreted by macrophages [28], elevated in DM-ILD compared with DM without ILD [29], and correlated with the severity of pulmonary disease [30].…”
Section: Introductionmentioning
confidence: 93%